BRANDING TECHNIQUES SUCCESSFUL YOUNG ENTREPRENEURS (PKM INTERNATIONAL ON NEW ENTREPRENEURSHIP) - Marthin Nanere; Steven Siaila; Fransiska Natalia Ralahallo; Evracia Turukay; Erfendi Regar (Universitas Pahlawan Tuanku Tambusai, 2025)
Entrepreneurship is one of the keys to enhancing the economic independence of society, especially amidst the challenges of the global economy and digital transformation. This service program aims to provide training and counselling to students and alumni of the Management Department who are also entrepreneurs, in order to enhance their skills and understanding in managing independent businesses. The methods used include interactive workshops, case-based business simulations, and personal mentoring. The results show a significant improvement in participants' understanding of basic entrepreneurship concepts, financial management, and digital technology adaptation strategies. In addition, changes in participants' mindsets regarding business risks and the importance of innovation were also achieved. This program successfully created an adaptive and innovative entrepreneurial community, thereby supporting the sustainable development of a locally-based economy. Keywords: Entrepreneurship, Economic Independence, Training and Counselling, Business Innovation, Financial Management, Digital Technology